2012
DOI: 10.1038/hr.2012.14
|View full text |Cite
|
Sign up to set email alerts
|

Exaggerated blood pressure response during exercise treadmill testing: functional and hemodynamic features, and risk factors

Abstract: The factors which contribute to an exaggerated blood pressure response (EBPR) during the exercise treadmill test (ETT) are not wholly understood. The association between the insertion/deletion polymorphisms of the angiotensin-converting enzyme (ACE) and M235T of the angiotensinogen with EBPR during ETT still remains unstudied. To identify and compare the risk factors for hypertension between normotensive subjects with EBPR and those who exhibit a normal curve of blood pressure (BP) during ETT. In a series of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Such an effect might have a greater influence on vascular reactivity than on basal tone. [16][17][18][19] Therefore, although resting BP may not necessarily be high when the vascular impairment is not yet very severe, the vascular reactivity may already be abnormal, possibly resulting in excessive BP elevation under stressful conditions, for example, during physical exertion.…”
Section: Introductionmentioning
confidence: 99%
“…Such an effect might have a greater influence on vascular reactivity than on basal tone. [16][17][18][19] Therefore, although resting BP may not necessarily be high when the vascular impairment is not yet very severe, the vascular reactivity may already be abnormal, possibly resulting in excessive BP elevation under stressful conditions, for example, during physical exertion.…”
Section: Introductionmentioning
confidence: 99%
“…Sympathetic tone is generally more activated in individuals with, than without, metabolic syndrome. Thus, the findings of Lima et al 4 in which age and BMI are significantly associated with exercise-induced hypertension or EBPR are logical and rational. Table 1 shows that the cumulative increase in mean systolic blood pressure among older adult men is larger in response to a work load expressed as a METS increase (work load progress).…”
mentioning
confidence: 95%
“…However, they found no significant relationships. Others have found that the exercise-induced hypertension expressed as EBPR by Lima et al 4 correlates with subsequent cardiac events 5 in patients with cardiovascular diseases. In addition, a hypertensive blood pressure response to exercise in healthy individuals can predict the development of hypertension.…”
mentioning
confidence: 96%
See 2 more Smart Citations